Composable mediation for security-aware mobile services. - Tarkoma, Sasu (IEEE Communications magazine)
This article shows how service mediation can be used to add security features to services in a mobile service platform. This base platform takes care of security, charging, and other basic functions, which are then configured for services at runtime using a pluggable mediator framework. Service providers can focus on content, and thus leverage the signaling and mediation capabilities of the core platform. Mediators add specific functionality to a service, and are a specific form of service composition and selection. We examine how security technologies for authentication and authorization are integrated by mediators into a single policy infrastructure with a homogeneous interface for services. We consider here the Web services SAML and the 3GPP GBA security bootstrapping standard in the context of mobile services. We give an example using a video on demand service, and discuss how and when security concerns of services can be transferred from the services to mediators.